1989
DOI: 10.1002/bin.2360040205
|View full text |Cite
|
Sign up to set email alerts
|

A sustained analysis of the behaviors of schooling

Abstract: Educationally significant behaviors of students, teachers, and supervisors were directly assessed daily for a fiscal year in a residential school in which the results of behavior analysis research are applied to all levels of schooling. The variables assessed included those found to be concomitantly related to effective schooling as determined by the educational research literature, and functionally related to effective teaching as determined by the literature of behavior analysis. Weekly summaries of the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 17 publications
3
47
0
Order By: Relevance
“…Results demonstrated the utility of both written and vocal learn units in producing higher rates of correct academic responding and an increase in the achievement of instructional objectives. These findings were consistent with results obtained by Ingham & Greer (1992), Selinske et al (1991), Greer et al (1989), and Lamm & Greer (1991). Based on these studies, it was found that increasing the number of learn units that were sequenced carefully and that were accurately consequated by teacher and supervisor behaviors led to (1) an increase in correct academic responses, (2) higher numbers of achieved objectives and (3) fewer incorrect responses.…”
Section: The Learn Unitsupporting
confidence: 93%
See 2 more Smart Citations
“…Results demonstrated the utility of both written and vocal learn units in producing higher rates of correct academic responding and an increase in the achievement of instructional objectives. These findings were consistent with results obtained by Ingham & Greer (1992), Selinske et al (1991), Greer et al (1989), and Lamm & Greer (1991). Based on these studies, it was found that increasing the number of learn units that were sequenced carefully and that were accurately consequated by teacher and supervisor behaviors led to (1) an increase in correct academic responses, (2) higher numbers of achieved objectives and (3) fewer incorrect responses.…”
Section: The Learn Unitsupporting
confidence: 93%
“…Recently, "learn units" have been identified within the field of education: "The learn unit consists of the interlocking operants of instruction that incorporate particular student and teacher interactions that predict whether student behavior will be controlled by particular stimuli and setting events" (p. 161) . The learn unit measurement has served to produce better research to help children with various needs (Albers & Greer, 1991;Kelly & Greer, 1996;Martinez, 1996;Hogin, 1996;Lindhart-Kelly & Greer, 1997), improve teacher training procedures (Keohane, 1997;Ingham & Greer, 1992), and determine more accurate measures of school-wide effectiveness (Greer, McCorkle, & Williams, 1989;Selinske & Greer, 1991;Lamm & Greer, 1991).…”
Section: The Effects Of Learn Units On Student Performance In Two Colmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, in the studies comparing percentage mastery versus fast rate mastery, inevitably the participants who received rate instruction also received more instructional presentations. Recently, investigators have isolated the instructional unit that predicts learning, the learn unit (Albers & Greer, 1991 ;Emurian, Hu, Wang , & Durham , 2000;Emu rian , 2004;Greer & McDonough, 1999;Greer, McCorkle, & Williams, 1989;Ingham & Greer, 1992;Selinske, Greer, & Lodhi , 1991). A learn unit includes the teacher or automated teaching device ensuring the student's attention, the unambiguous delivery of an antecedent that is to be the discriminative stimulus when the student has mastered the discriminated operant, and delivery of either a reinforcer or a correction .…”
mentioning
confidence: 99%
“…Participants were three children, Marcelo (male, 5 years, 0 months old), Marta (female, 4 years, 7 months old), and Ana (female, 5 years, 11 months old), who were diagnosed with autism and received individualized teaching in a behavioral program with CABAS© components (e.g., Greer et al 1989) for 25 h per week at the Centro Al-Mudarïs in Cordoba, Spain. All of the children were Spanish speakers and the procedures were conducted in Spanish.…”
Section: Participantsmentioning
confidence: 99%